Awareness Study On The Quality Assessment System In Construction (Qlassic) For Construction Works In Pulau Pinang - Yusoff, Muhammad Firdaus (Universiti Sains Malaysia, 2017)
The Construction Industry Standard (CIS 7:2006) on Quality Assessment System (QLASSIC) was developed in November 2006 to evaluate and improve the quality of the building construction work among the developers and contractors. QLASSIC sets out the standards for the quality of workmanship for various construction elements of building and also infrastructure works. QLASSIC is not fully implemented and applied by all developers and contractors in Pulau Pinang as this element is not a compulsory requirement in getting projects. Moreover, there are only small numbers of developers And Contractors who are aware on the benefits of the application of QLASSIC in their construction projects. Besides, there are some barriers that cause those parties to avoid using QLASSIC. The aim of this study is to study on the challenges of QLASSIC assessment and its acceptance by Developers and Contractors that register under the CIDB, Malaysia for the construction projects in order to achieve the standard of quality in construction in terms of workmanship. Data was collected from the literature study and from Construction Industry and Development Board (CIDB) by means of interviews and questionnaires. Based on the analysis, most of the developers and contractors are still not familiar with QLASSIC. The barriers that contributed to developers and contractor refusal to comply with QLASSIC are unfamiliar with QLASSIC system, less of technical personnel during the QLASSIC assessment, less of QLASSIC’s assessors and low reputation if QLASSIC score less than CIDB’s requirement. Most of the respondents in the developers companies agree with the barrier in which the main reason that stops them from applying QLASSIC is that the project cost will increase and project period will delayed.